Research of 5G NR RedCap technology - Hanyang LI; Weiwen WENG; Nan LI; Long ZHANG; Jinxia CHENG (Dianxin kexue)
Faced to industrial wireless sensors, video surveillance, wearable devices, RedCap UE (reduced-capability user equipment) was proposed in 3GPP Release 17 (Rel-17), which could greatly reduce the costs of UE under the premise of satisfying the requirements of these use cases.Firstly, the standardization progress of 5G RedCap was introduced.Then, typical use cases of 5G RedCap technology were analyzed.After that, deep research was carried on the complexity reduction characteristics as well as the related gains brought by RedCap technology from two aspects of UE optimization and network performance improvement.Finally, the development potential and the evolution direction in the future were summarized.